Bi-Level Positive Airway Pressure for Non-invasive Respiratory Support of Foals - Raidal, Sharanne L.; Catanchin, Chee Sum Melanie; Burgmeestre, Lexi; Quinn, Chris T. (Frontiers in Veterinary Science, 2021)
Respiratory insufficiency and pulmonary health are important considerations in equine neonatal care. As the majority of foals are bred for athletic pursuits, strategies for respiratory support of compromised foals are of particular importance. The administration of supplementary oxygen is readily implemented in equine practice settings, but does not address respiratory insufficiency due to inadequate ventilation and is no longer considered optimal care for hypoxia in critical care settings. Non-invasive ventilatory strategies including continuous or bi-level positive airway pressure are effective in human and veterinary studies, and may offer improved respiratory support in equine clinical practice. The current study was conducted to investigate the use of a commercial bilevel positive airway pressure (biPAP) ventilator, designed for home care of people with obstructive respiratory conditions, for respiratory support of healthy foals with pharmacologically induced respiratory insufficiency. A two sequence (administration of supplementary oxygen with, or without, biPAP), two phase, cross-over experimental design was used in a prospective study with six foals. Gas exchange and mechanics of breathing (increased tidal volume, decreased respiratory rate and increased peak inspiratory flow) were improved during biPAP relative to administration of supplementary oxygen alone or prior studies using continuous positive airway pressure, but modest hypercapnia was observed. Clinical observations, pulse oximetry and CO2 monitoring of expired gases were of limited benefit in identification of foals responding inappropriately to biPAP, and improved methods to assess and monitor respiratory function are required in foals.